Design of a 4-bit ripple adder using Quantum-dot Cellular Automata (QCA) - Chan S.T.Y.; Chau C.F.; Bin Ghazali A. (IEEE Computer Society, 2023)
Quantum-dot Cellular Automata (QCA) is one of the new emerging nanotechnologies explored as an alternative to current CMOS designs. This paper presents the fundamental concepts of QCA and QCA-based logic design. Basic QCA logic circuits such as the inverter, three-input majority gate and five-input majority gate are studied and implemented using QCADesigner. To demonstrate the practical use of using QCA in logic design, a 4-bit ripple adder using a combined concepts from the conventional RCA and CLA is proposed using 20 three-input majority gates, 4 five-input majority gates and 12 inverters. The proposed adder uses 1246 cells which resulted in an area of 1.75um 1.43um, and a latency of 5.75 clock cycles. 2013 IEEE.